Impact of global climate change on the health, welfare and productivity of intensively housed livestock - Kuczynski, Tadeusz; Blanes-Vidal, Victoria; Li, Baoming; Gates, Richard S; Alencar Naas, Irenilza de; Moura, Daniella J; Berckmans, Daniel; Banhazi, Thomas M (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: Major scientific studies have shown that global warming (i.e. increasing average temperature of the Earth) is now a reality. The aims of this paper are to broadly review the underlining causes of global warming, the general effects of global warming on social and environmental systems and the specific effects of resulting from global warming phenomena severe fluctuations in weather patterns, particularly heat waves on livestock health, welfare and productivity. Finally this article aims to summarise some common sense climate control methods and more importantly to highlight the required future research and development (R&D) work that is necessary to achieve a new level of building environment control capability, and thus ensure that the intensive livestock industries will be able to cope with the changed external climate. With the increasing temperatures on a global scale, the most direct effect of the high temperature on the animals is heat stress, which has been proven to have a variety of negative effects on animal health, welfare and productivity. Different potential measures could be taken in future to alleviate the increased heat stress. Some of these measures are mere adaptations or improvements of current engineering solutions. However, facing the complex challenges of global warming and particularly resulting from it the rapid increase of the number of consecutive days with significantly higher than average temperatures will probably require novel solutions, including new designs based on solid engineering judgment, development of new engineering standards and codes to guide designs, the exploration of new and superior building materials, the need for better energy management, and the development of substantially more “intelligent” control systems that will balance changing exterior disturbances, interior building loads and demands to the biological needs of the occupants of the structures. Keywords: livestock, global climate change, greenhouse effect, animal welfare, heat stress, temperature, cooling, agricultural buildings DOI: 10.3965/j.issn.1934-6344.2011.02.001-022 Citation: Kuczynski T, Blanes-Vidal V, Li B M, Gates R S, Nääs I A, Moura D J, Berckmans D, Banhazi T M. Impact of global climate change on the health, welfare and productivity of intensively housed livestock. Int J Agric & Biol Eng, 2011; 4(2): 1<span style="line-height: 130%; font-family: